THE IMPLEMENTATION OF TEACHING SPEAKING TO YOUNG ADULT LEARNERS IN ENGLISH MASSIVE KEDIRI - Nopitasari, Indah; Nurhajati, Diani; Susanti, Yunik (JURNAL KOULUTUS, 2024)
This research aims at describing the implementation of teaching Speaking by a tutor for young adult students in one location, which focuses on instructional materials, learning activities, and learning steps in class. This case study was conducted using a qualitative approach. The subjects of this research were a tutor and two participants at the Ngampel spot, Mojoroto Kediri. The researchers carried out observations, interviews and documentation to collect data. The findings show that the implementation of learning speaking skills in young adult groups at English Massive is interesting in terms of the material and teaching techniques. When teaching, the tutor always chooses activities that train speaking skills and completed with interesting learning media.